Pope Gregory's letter-bearers : a study of the men and women who carried letters for Pope Gregory the Great - Martyn, John R. C. (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
"With the Lombards invading Italy, and Slavs invading Illyria, and very active slave-dealers at work, the number of men and women who reached Rome and carried a papal letter, to sort out a legal or personal problem at home, is quite surprsing, considering the slowness and the very real dangers of often long journeys in boats or on horseback. ... [T]hey came from all over the civilized world, many briefly appearing on the stage, their mission quite often not reported later on."--Cover, p. [4].
Includes bibliographical references (p. [115]-124) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Gregory -- I, -- Pope, -- ca. 540-604 -- Correspondence; Church history -- Middle Ages, 600-1500.; Popes -- Correspondence -- History; Electronic books